PERANCANGAN GELANGGANG REMAJA SEBAGAI MEDIA EKSPRESI DAN KEBERSAMAAN REMAJA PENYANDANG ATTENTION DEFICIT HYPERACTIVITY DISORDER DI JAKARTA BARAT - Laurencia Josita; Rudy Surya (Jurusan Arsitektur dan Perencanaan, 2023)
ADHD (Attention-Deficit/Hyperactivity Disorder) is a mental disorder that is common in childhood to adolescence. The adolescents referred to in this study are residents aged 10-19 years. Symptoms of ADHD in adolescents can reduce the quality of life and have an impact on social development, this can cause various problems for their social life. It is important for youth with ADHD to develop a sense of community and know that they are not alone. A youth center can help adolescents with ADHD in this aspect as well as a medium for channeling their energy. Youth center is a place for teenagers to do positive activities in their free time. Using a qualitative method by conducting observations, interviews, and literature on research subjects, the project designed a youth center that can build a sense of togetherness in the community of adolescents with ADHD with a sensory approach. The project location is in the Kedoya area, West Jakarta. The result of the research is a three-storey building with various applications of sensoric approach. The result of the design is a three-storey building with various applications of sensory approaches. Within the building there are: dance studios, ADHD community rooms, cafes, amphitheater, ADHD study rooms, basketball courts, music studios, art workshops and a rooftop garden which functions to support the needs and characteristics of adolescents with ADHD. The program was chosen considering the project's theme, namely togetherness and creativity so that programs tend to have activities that require collaboration or meeting other people. Keywords: ADHD ; Togetherness; Youth Center Abstrak ADHD (Attention-Deficit/Hyperactivity Disorder) merupakan salah satu penyakit gangguan mental yang umum terjadi pada masa anak-anak hingga remaja. Remaja yang dimaksud dalam penelitian ini adalah penduduk yang berusia 10-19 tahun. Gejala ADHD pada remaja dapat menurunkan kualitas hidup dan memiliki dampak termasuk dalam perkembangan sosial, hal ini dapat menimbulkan berbagai masalah bagi kehidupan sosial mereka. Penting bagi remaja penyandang ADHD untuk membangun rasa komunitas dan mengetahui bahwa mereka tidak sendiri. Sebuah gelanggang remaja dapat membantu remaja penyandang ADHD dalam aspek tersebut sekaligus sebagai media untuk menyalurkan energi mereka. Gelanggang remaja adalah sebuah tempat untuk remaja beraktivitas positif dalam waktu luangnya. Menggunakan metode kualitatif dengan melakukan observasi, wawancara, dan studi pustaka terhadap subjek penelitian, maka proyek merancang sebuah gelanggang remaja yang dapat membangun rasa kebersamaan dalam komunitas remaja penyandang ADHD dengan pendekatan sensorik. Lokasi proyek berada di daerah Kedoya, Jakarta Barat dengan. Hasil rancangan adalah bangunan tiga lantai dengan berbagai pengaplikasian pendekatan sensorik. Dalam bangunan terdapat: studio menari, ruang komunitas ADHD, cafe, amphitheater, ruang studi ADHD, lapangan basket, studio musik, workshop seni dan rooftop garden yang berfungsi untuk menunjang keperluan dan sifat remaja penyandang ADHD. Program dipilih mengingat tema proyek yaitu kebersamaan serta kreativitas sehingga program cenderung memiliki aktivitas yang membutuhkan kerja sama atau bertemu dengan orang lain.